تحسين الخدمة العمومية من البيروقراطية إلى الخوصصة-ماليزيا نموذج ا - - زبيري رمضان (Hakika (The Truth) Journal for Social & Human Sciences, 2025)
The traditional concept of bureaucratic management is no longer capable of dealing with the accelerating demands imposed by the logic of the new public service in the era of globalization and standardization; rationalization and quality; new public management; governance; and even the reinvention of government. The appropriate privatization of local services requires most developing countries to abandon the traditional, inefficient, and costly bureaucratic approach in favor of strengthening the role of the private sector in providing public services and goods. The study examined the case of Malaysia as a model--from which Algeria can benefit--as a successful experience in the field of development and improving public service. This experience was distinguished by its ability to maximize the exploitation of human and material resources due to the growing and vital role of the private sector and the integration of its working mechanisms into government management, thereby benefiting from international and regional variables to increase the competitiveness and quality of local goods and services provided (ISO).